Texas Christian Advocate - (:unkn) unknown (My University, 1878)
Original microfilm produced by the Bridwell Library at Southern Methodist University.
Volume 1, Number 1 of The Texas Christian Advocate was issued in 1854. It operated as the official organ of Texas Conferences of the Methodist Episcopal Church, South. Eventually this went on to include the conferences in Texas, New Mexico, and Oklahoma by 1917. The newspaper was published initially in Galveston, but the publication moved to Dallas in 1887.
Keywords: Galveston (Tex.)--Newspapers.; Galveston County (Tex.)--Newspapers.; Methodist Episcopal Church, South--Newspapers.